Optimization of culture conditions for exopolysaccharides production in Rhizobium sp. using the response surface method - Pereira Duta, Flávia; Pessôa de França, Francisca; de Almeida Lopes, Léa Maria (Electronic Journal of Biotechnology, 2006)
The combined effects of the processing parameters for exopolysaccharides production by Rhizobium sp. was studied using the experimental design and response surface methodology. The experiments were carried out using a fermenter with 20 L capacity, as the reactor. All processing parameters were online monitored. The temperature [(30 ± 1)ºC] and pH value (7.0 ± 0.1) were kept constant throughout the experimental time. As statistical tools, a complete 23 factorial planning with central point and response surface were used to study the interactions among three relevant variables of the fermentation process: calcium carbonate concentration, aeration and agitation. The processing parameters setup for reaching a maximum response for exopolysaccharides production was obtained when applying the highest values for calcium carbonate concentration (1.1 g/L), aeration (1.3 vvm) and agitation (800 rpm). In addition, the combination of these optimum processing parameters yielded YP/S (g/g) = 0.35.